Portrait of Attendees at the 277th Annual California Real Estate Association Convention - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing attendees of the 277th Session of the California Real Estate Association, held at the San Jose Civic Auditorium, May 24-26 1951.